(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s ((3eOjfI jRO s)
(3ChdgG (B:s
(3hHYO , aEf CYXe GdYdhe ebOQkG hGQaYgG TQakG hefGQkG Yde GdJaSjQ GdPi gh QFjS GdYdhe GdOjfjI hQCSgG , heHfi bhGYO GdTQY hCSGSgG s
(3BNQgG (B:s
(3BNQg ef ShQg GdfGS bhdg (B: (3Yf GdfHi Udi Gddg Ydjg hSde (B: (3ef bQC ShQI GdeYhPJjf acCfeG bQC GdcJH GdJi CfRdgG Gddg JYGdi hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi ghGeTgG JbjjOGJ hJUMjMGJs
(3hcJH GdBjGJ GdcQjeI HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdJaSjQ hYdhe GdbQBfs